Information and communication technology based prompting for treatment compliance for people with serious mental illness - Kauppi, Kaisa (Cochrane Database Syst Rev, 2014)
BACKGROUND: Non‐compliance is a significant problem among people with serious mental disorders, presenting a challenge for mental health professionals. Prompts such as telephone calls, visits, and a posted referral letter to patients are currently used to encourage patient attendance at clinics and/or compliance with medication. More recently, the use of information and communication technology (ICT)‐based prompting methods have increased. Methods include mobile text message (SMS ‐ short message service), e‐mail or use of any other electronic device with the stated purpose of encouraging compliance. OBJECTIVES: To investigate the effects of ICT‐based prompting to support treatment compliance in people with serious mental illness compared with standard care. SEARCH METHODS: We searched the Cochrane Schizophrenia Group’s Trials Register (31(st) May 2011 and 9(th) July 2012) which is based on regular searches of CINAHL, BIOSIS, AMED, EMBASE, PubMed, MEDLINE, PsycINFO, and registries of clinical trials. Also, we inspected references of all identified studies for further trials and contacted authors of trials for additional information. SELECTION CRITERIA: Relevant randomised controlled trials involving adults with serious mental illness, comparing any ICT‐based prompt or combination of prompts by automatic or semi‐automatic system compared with standard care. DATA COLLECTION AND ANALYSIS: Review authors reliably assessed trial quality and extracted data. We calculated risk ratio (RR) with 95% confidence intervals (CI) using a fixed‐effect model. For continuous outcomes, we estimated the mean difference (MD) between groups, again with 95% confidence intervals. A 'Summary of findings' table using GRADE was created, and we assessed included studies for risk of bias. MAIN RESULTS: The search identified 35 references, with 25 studies, but we could only include two studies with a total of 358 participants. The studies had a moderate risk of bias, and therefore risk overestimating any positive effects of ICT‐based prompting. Both included studies compared semi‐automatised ICT‐based prompting intervention with standard care groups in mental health outpatient care. The interventions were SMS‐message and an electronic assistant device. One included study reported our primary outcome, compliance. There was not any clear evidence that ICT‐based prompts increase improvement in compliance (stop taking medication within six months n = 320, RR 1.11 CI 0.96 to 1.29, moderate quality evidence). There was some low quality evidence that ICT‐based prompts have small effects for: mental state (average change in specific symptom scores within three months n = 251, MD ‐0.30 CI ‐0.53 to ‐0.07; severity of illness within three months n = 251, MD ‐0.10 CI ‐0.13 to ‐0.07 and six months n = 251, MD ‐0.10 CI ‐0.13 to ‐0.07; average change in depressive scores within six months n = 251, RR 0.00 CI ‐0.28 to 0.28; global symptoms within three months n = 251, MD ‐0.10 CI ‐0.38 to ‐0.07; negative symptoms within three months n = 251, MD ‐0.10 CI ‐0.38 to 0.18 and six months n = 251, MD ‐0.30 CI ‐0.58 to 0.02, low quality evidence). Level of insight improved more among people receiving ICT‐based prompt compared with those in the control group at six months (n = 251, MD ‐0.10 CI ‐0.13 to ‐0.07). ICT‐based prompts also increased quality of life (average change in quality of life within six months n = 251, RR 0.50 CI 0.19 to 0.81, moderate quality evidence). Based on the existing data, there is no evidence that either intervention is less acceptable than the other (n = 347, 2 RCTs, RR 1.46 CI 0.70 to 3.05, low quality evidence). Included studies did not report outcomes of service utilisation, behaviour, costs or adverse events. AUTHORS' CONCLUSIONS: The evidence base on the effects of ICT‐based prompts is still inconclusive. Data to clarify ICT‐based prompting effects are awaited from an ongoing trial, but further well‐conducted trials considering the different ICT‐based prompts are warranted.